Correlations between sex-related hormones, alcohol dependence and alcohol craving - Ho, Ada M.-C.; Geske, Jennifer R.; Bakalkin, Georgy; Winham, Stacey J.; Karpyak, Victor M. (Drug and alcohol dependence, 2019)
•Plasma FSH level is higher in alcohol-dependent men (AD) compared to controls.•Plasma FSH, testosterone and progesterone levels correlate with craving in AD men.•Sex-related hormone levels may play a role in alcoholism and related phenotypes. Sex-related differences in the susceptibility, progression, and treatment response in alcohol-dependent subjects have been repeatedly reported. In this study, we aimed to investigate the associations of the sex-related hormone/protein levels with alcohol dependence (AD) and alcohol craving in male and female subjects. Plasma sex-related hormones (estradiol, estrone, total testosterone, progesterone, follicle stimulated hormone [FSH], luteinizing hormone), and sex hormone binding globulin were measured by mass spectrometry or automated immunoassays from 44 recently-abstained subjects (29 males and 15 females; mean age = 45.9 ± 15.6) meeting DSM-IV-TR criteria for AD and 44 age-, sex- and race-matched non-AD controls. Conditional logistic regression was conducted to examine the association of sex-related hormone and protein levels with AD risk, accounting for matching variables. Their associations with alcohol craving scales (Penn Alcohol Craving Scale and Inventory of Drug-Taking Situations) were assessed in AD subjects. Plasma FSH level was significantly higher in AD males (10.3 ± 9.8 IU/L) than control males (8.0 ± 15.9 IU/L; p = 0.005, pcorrected = 0.035). We also found a significant inverse correlation of FSH level with propensity to drink in negative emotional situations (Spearman’s rho=-.540; p = 0.021) and positive correlations between progesterone level and craving intensity (Spearman’s rho=.464; p = 0.020) and between total testosterone level and propensity to drink under temptations (adjusted for no-drinking days; β=6.496; p = 0.041) in AD males. These results suggest that FSH, progesterone, and testosterone levels may be associated with AD and alcohol craving in AD males. Future research is needed to replicate these findings and investigate the underlying biological mechanisms.